High Larval Concentrations and Onshore Transport of Barnacle Cyprids Associated With Thermal Stratification - Yamhure, Gabriela M.; Reyns, Nathalie; Pineda, Jesús (Frontiers in Marine Science, 2021)
To better understand the hydrodynamic and hydrographic conditions experienced by larvae in the nearshore (within 1km of shore), and the role that larval behavior plays in mediating shoreward transport to adult benthic habitats, we examined the vertical distribution and concentration of barnacle cyprids in a shallow, nearshore region in southern California, USA. We collected high-resolution physical measurements of currents and temperature at 3 stations (8m, 5m and 4m depths), and high-frequency measurements of barnacle larvae at a 4m deep station 300 m from shore. Larvae were sampled from distinct 1m depth intervals between the surface and the bottom (0-1m, 1-2m, 2-3m, 3m-bottom), each hour for overnight periods that ranged between 13 to 24-hours in five cruises during the summers of 2017 and 2018. Barnacle cyprids of Chthamalus fissus predominated in all samples. Thermal stratification decreased closer to shore, but when the nearshore-most station remained stratified (Δ°C m-1 ≥ 0.1), C. fissus cyprid concentrations were high to extremely abundant (exceeding 200 and 4000 individuals m-3, respectively). There were significant positive correlations between thermal stratification and the log-transformed C. fissus concentration at cruise-to-cruise scales, and between stratification and vertical variability in the high-frequency cross-shore currents at 2-day scales. Additionally, estimated larval transport was relatively high and shoreward when nearshore thermal stratification was greatest. Significant, albeit small, diel differences in cyprid distributions were also observed, with the proportion of cyprids increasing near the surface at night, and concentrations greater during the day than at night. Collectively, these results suggest that thermal stratification increases larval supply to the nearshore, and may enhance onshore larval transport to augment chances of successful settlement and recruitment to the intertidal adult habitat.